Percepção e territorialidade no Parque Itaimbé de Santa Maria/RS - Cruz, Claudete Robalos da (2009)
This study aimed to understand the process of formation of territoriality from the biological and cognitive perception (Maturana, 1995) who frequented the park Itaimbé Santa Maria / RS. Perception is defined as a configuration object for the conduct. The conduct, in turn, presents itself as a discursive action that builds and re-build in the geographic space, turning it constantly, setting territoriality. Humanistic Geography and the phenomenological method served as philosophical contribution of the research, because of its commitment to understanding the phenomena not only through observation, but the lived space of immediate experience. Discourse analysis was chosen as the research methodology, whose purpose was to record how the language expresses the perception and behavior as manifested in perception. To this end, we adopted as a tool for collection and analysis of the perceptions, three themes with guiding questions. Thus, through the perceptions of park goers Itaimbé Santa Maria / RS, it was possible to identify the functionality, territoriality and understand the meaning and the relations established between the park goer. As regards the features of the park Itaimbé respondents, there are two specific functions, one appointed by the individuals who use this space as a result of recreational activity and the other by those who do their daily work there, thus revealing two large groups of goers. Indeed, it was observed that these groups are not hegemonic groups in relation to identity, but heterogeneous and dynamic contributing to the establishment of territoriality in the park Itaimbé Santa Maria / RS. Thus, the territoriality were diagnosed by identifying the reasons why the frequently uses the geographical area studied, and mapped into 6 subgroups. Accordingly, the definition of perception as object configuration for the conduct, enabled to understand that perception is not a representation of a world pre-determined, or the territory is perceived as stable as a result of a territorial or political, but as a function of conduct. Thus, territoriality has not immutable, but transient and flexible as the conduct of the postmodern subject.